EFFECT OF FASN AND ANXA9 GENE POLYMORPHISM ON GENETIC VARIATION, QUANTITATIVE AND ECONOMIC IMPACT OF LAMB'S WEANING WEIGHT - Senkal, Riyadh Hamad; Al-Jubori, Omar Sadeq Hameed; ALmaamory, Yasseen Abdulsalam Husain ALmaamory; Abdulkareem, Talal Anwer (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The objective of the current study was to investigate the effect of FASN AND ANXA9 gene polymorphism on genetic variation, quantitative and economic influences, and the extent of their contribution to the variation in the weaning weight of Awassi lambs based on the genetic polymorphism of their dams. New equations were designed and modified to calculate the contribution of both genes to the weight and price of the lambs. The contribution of both genes to the heritability of lamb's waning weight and the expected quantitative and price values to be inherited by the next generation were also estimated. Results revealed that the AA genotype of the FASN gene was superior to its hetero genotype AT counterpart in price and quantitative values. Moreover, the FASN gene was superior to the ANXA9 gene in both counterpart values. In conclusion, The FASN gene can be adopted as linked to the lamb's weight. It is considered an influential and effective gene in the studied trait and can be relied upon in selecting the dam ewes in the sheep flocks.